Hubungan Perilaku Caring Perawat Dengan Tingkat Kecemasan Pasien Di Ruang Rawat Inap Anggrek Rumah Sakit Umum Daerah Talaud - Mataputun, Aglin; Pondaag, Ferlan; Kundre, Rina (Mapalus Nursing Science Journal, 2025)
Background: Caring can improve the health and welfare of patients and make it easier for nurses to provide health services. Nurses who apply caring play an important role in increasing patient self-confidence and reducing anxiety levels. Reducing anxiety and stress will strengthen the body's defense system, thereby supporting the healing process optimally. Objective: To determine the relationship between nurses' caring behavior and patient anxiety levels in the Anggrek inpatient room at Talaud Regional General Hospital. Method: This type of research uses a cross sectional approach with quantitative research methods, using the Spearman correlation test. The sample used was 50 respondents calculated using the Slovin formula with a purposive sampling technique based on inclusion criteria. The instrument used to measure nurses' caring was a caring behavior questionnaire with 41 questions and to measure patient anxiety using the HARS questionnaire with 14 statements analyzed using SPSS version 29. Results: There was a relationship between nurses' caring behavior and the level of anxiety in the weak category with (p-value = 0.026) and strength of correlation (-0.160). Conclusion: there is a relationship between caring nurses and the level of patient anxiety in the Orchid inpatient room at Talaud Regional General Hospital.